Introduction to website development technologies - Williams, Trevoir (Packt Publishing, 2022)
Learn how to build a website using HTML and CSS and Visual Studio Code from scratch About This Video Learn to build and deploy a multi-page website from scratch Learn the process of publishing your static website to the internet using Netlify Learn to write JavaScript and jQuery In Detail The content of this course assumes no prior knowledge of programming or web development and will teach you how to set up an environment to develop a website from scratch; all the way up to deploying it on the Internet for the world to see. This is a short course with just over five hours of content but smartly broken up to highlight a set of related activities based on each module in the application that is being built. We will also look at troubleshooting and debugging errors as we go along; implementing best practices; writing efficient logic and understanding why developers do things the way they do. Your knowledge will grow, step by step, throughout the course and you will be challenged to be the best you can be. By the end of this course, you will have moved around in Visual Studio Code and examined errors so much, that it will be second nature for you when working in the web development environment. This will put your newly learned skills to practical use and impress your boss and coworkers. Audience This course requires no prior experience with any programming language, making it ideal for anyone interested in learning basic web development.
"Updated in May 2022.". - Online resource; title from title details screen (O'Reilly, viewed June 27, 2022)
Keywords: Web site development; HTML (Document markup language); Sites Web; Développement; HTML (Langage de balisage); HTML; Instructional films; Internet videos; Nonfiction films; Films de formation; Films autres que de fiction; Vidéos sur Internet